PROTON DRIPLINE FOR ISOTONE N = 18, 20, AND 22 USING MODIFIED RELATIVISTIC MEAN FIELD (MRMF) MODEL - Jenny Primanita Diningrum; Anto Sulaksono (Program Studi Fisika Universitas Negeri Jakarta, 2019)
Determining the position of one- and two-proton dripline for isotone of N = 18, 20, and 22 has been studied through Modified Relativistic Mean Field (MRMF). The model exemplifies three impacts, namely isovector-isoscalar coupling, tensors, and electromagnetic exchange through five parameter set variations. The position of one- and two-proton dripline for the isotones is predicted by applying two methods, which are two-proton separation energy, and Fermi energy. The research shows that the prediction of one- and two-proton dripline for isotone of N = 18, and N = 20 is positioned at Z = 22 and Z = 26 consecutively. Then, the prediction of one- and two-proton dripline for isotone of N = 22 has two positions, Z = 26 and Z = 28. The calculation result indicates that the position prediction for isotone of N = 18, N = 20, and N = 22 is following the research result conducted by Nazarewicz with RMF+NLSH model [1]. Meanwhile, isovector-isoscalar coupling, tensors, and electromagnetic exchange do not affect massively for the position prediction of two-proton dripline. However, the three methods affect one-proton dripline.